RANCANG BANGUN ALAT PENGGANTIAN AIR DAN PEMBERIAN PAKAN SECARA OTOMATIS PADA AKUARIUM IKAN HIAS BERBASIS MIKROKONTROLER - Hendry, Hendry Prayoga; Hidayati, Qory; Aditya, Angga Wahyu (JIMREK : Jurnal Ilmiah Rekayasa Elektro, 2025)
The research entitled "Design of Water Replacement Equipment and Automatic Feeding in Microcontroller-Based Ornamental Fish Aquarium" is a development research on aquarium media for ornamental fish. This study aims to create a system where the system can work for water replacement, feeding, and automatic lighting in the aquarium automatically. This study uses Arduino Mega as a microcontroller board, turbidity sensor as a detector of turbidity in water, Real Time Clock IC DS1307 as an electronic clock to calculate real time conditions, Selenoid Valve as a valve that will be driven by solenoid electricity, Relay as an electronic switch, Liquid Cristal Display (LCD) to display text, Servo Motor as accelerometer and system speed control, ultrasonic sensor as signal detector, and pump used to drain liquid from lowlands to highlands. The results of this study show the tools that have been tested such as testing the RTC module which shows the RTC is connected to Arduino and LCD, testing the turbidity sensor which shows success in detecting water, testing the proximity sensor which shows an average difference in water of 1%, testing servo motor sensors that have worked quite well, testing the relay module for ON and OFF conditions get good information, testing the system as a whole that all systems work well according to what has been designed.